A comprehensive review on ethnomedicinal uses, phytochemistry, toxicology, and pharmacological activities of Dittrichia viscosa (L.) Greuter - Jerada, Rania; Er-Rakibi, Abdeljalil; Hassani, Abha Cherkani; Benzeid, Hanane; El Ouardi, Abdelmoula; Harhar, Hicham; Goh, Bey Hing *; Yow, Yoon Yen *; Ser, Hooi Leng *; Bouyahya, Abdelhakim; Mojemmi, Brahim; Doukkali, Anass (Elsevier, 2024)
Dittrichia viscosa is a perennial herb that has been used for generations in traditional medicine to address a variety of diseases, including diabetes, hypertension, cancer, microbial disorders, inflammatory conditions, and wound healing. The objective of this review is to provide an overview of existing knowledge on D. viscosa with regards to its botanical description, ethnomedicinal uses, and pharmacological properties. Databases such as Scopus, Wiley-Online, PubMed, Springer, Google Scholar, and ScienceDirect were used to select relevant articles based on their title and abstract.